Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jds.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and etiology of molar-incisor hypomineralization (MIH) in the city of Istanbul

Abstract: Background/purpose Molar-Incisor-Hypomineralisation (MIH) is the term used to depict a condition in which one or more of the permanent molar teeth and usually no less than one incisor tooth is hypomineralised and the prevalence rates vary from 2.4 to 40.2%. The aim of this study was to assess the prevalence and the risk factors of MIH in children in Istanbul, Turkey. Materials and methods A total of 1511 (760 M, 751 F), 8- to 11-year-old children were examined who had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
1
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 57 publications
(153 reference statements)
8
65
1
12
Order By: Relevance
“…Therefore, in this study, we examined birth data and the child's medical history in addition to giving more detailed information about the level and incidence of MIH, which is the strength of our study. As in many studies, there was no relationship between gender and MIH in our study. Zawaideh et al, however, reported the rate of MIH to be higher in girls and Jalevik et al to be higher in boys.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Therefore, in this study, we examined birth data and the child's medical history in addition to giving more detailed information about the level and incidence of MIH, which is the strength of our study. As in many studies, there was no relationship between gender and MIH in our study. Zawaideh et al, however, reported the rate of MIH to be higher in girls and Jalevik et al to be higher in boys.…”
Section: Discussioncontrasting
confidence: 57%
“…Similar to the studies of these two researchers, we observed PEB, atypical restoration, and extracted molar due to MIH in patients with preterm birth and low birthweight. There are also reports presenting different results, however; Koruyucu et al and Allazzam et al reported no relationship between low birthweight and MIH.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations